THE ROLE OF MOTIVATION AND WORKLOAD ON EMPLOYEE PERFORMANCE AT THE SADANANYA VILLAGE HEAD OFFICE CIAMIS REGENCY - Hilda Purnamawati; Malik Al Muslim Putra Dahlan; Iyan Sukiman (PT. Altin Riset Publishing, 2025)
This study aims to explore the implementation of Interpretation of Financial Accounting Standards (Human resource performance is a key pillar in the effectiveness of public sector organizations, including at the village government level which serves as the frontline of public service. This research is motivated by the phenomenon of declining employee performance at the Sadananya Village Head Office, Ciamis Regency. This initial indication is reinforced by internal assessment data, increasing absenteeism rates, and pre-survey findings that describe problems related to low work motivation and perceptions of excessive workload. Therefore, this study aims to analyze in depth the conditions of motivation (X₁), workload (X₂), and employee performance (Y), and to examine the influence of motivation and workload variables on employee performance partially and simultaneously. This study uses a quantitative approach with a descriptive verification design. The sampling method used is a census (saturated sample), where the entire population of 80 employees is used as respondents. Data collection was carried out through questionnaires, and the data analysis technique used is multiple linear regression analysis with the help of SPSS software. This study found that most employees experience low work motivation, while on the other hand they feel a high workload. The results of statistical testing then confirmed that these two factors, motivation and workload, were proven to have an influence on employee performance, both when analyzed separately (partially) and combined (simultaneously).